Problematika Peran Perbankan Dalam Regulasi Kelembagaan Pengelolaan Zakat (ZISWAF: Jurnal Zakat dan Wakaf, 2018)
The enactment of Law Number 23 Year 2011 on the Management of Zakat, making its own problems for sharia banking in helping the management of zakat. The role and function of sharia banking is not clear and weak. In addition to unclear, zakat management arrangements through sharia banking also pose legal political problems. This is because since the enactment of Law No. 23 of 2011 on the Management of Zakat is not accommodated expressly and concretely as an institution authorized as a manager of zakat. The vagueness of the role of sharia banking in zakat management regulation is a manifestation of vagueness and void of norms. Although the legal construction of banking roles and functions in accordance with Article 4 paragraph (2) of Law Number 21 Year 2008 concerning Sharia Banking is expanding, that is, syariah banking does not only carry out the activities of collecting funds and channeling public funds but can perform social functions as bait al-mall in collecting and distributing social funds of people as zakat. The enactment of the new zakat management law is expected to bring about big and positive changes, but in reality it seems not yet able to legally bind in applying the functions of zakat management.